(untitled) (Nepal Medical College Journal, 2020)
Adverse effects (AE) like vasovagal reactions (presyncope and syncope) have negative impact on old as well as new blood donors. Various methods have been suggested to prevent or attenuate AE in blood donors. This study assessed the effectiveness of prehydration with different fluids or applied muscle tension (AMT) during blood donation in preventing or attenuating AE. Consenting and eligible voluntary blood donors (n=448) were randomly allocated to Control (n=115), prehydration with 500 mL plain water (PW, n=97), prehydration with oral rehydration solution (ORS, n=71), prehydration with 400 mL fruit juice (FJ, n=74), or leg muscle tensing during blood removal (AMT, n=91) groups. Donors’ hemodynamic responses to blood donation were assessed by comparing blood pressures (systolic–SBP and diastolic–DBP) and heart rate (HR) recorded before blood removal to values midway during, and at 0 min, 5 min, 10 min and 15 min after blood removal. Presyncope and syncope were defined by BP and HR changes. Subjective AE were also recorded. Overall, 35 donors (7.8%) suffered AE with highest rates in PW (13.4%) and ORS (11.3%) groups and lowest in Control (3.5%) although group differences were not significant (p>0.05, Chi square). Blood removal was associated with significant falls in SBP and DBP (mean falls by 6.63 and 3.35 mmHg, respectively; p<0.001) but an insignificant rise in HR (mean increase by 0.67 bpm, p>0.05). Hemodynamic responses showed significant differences between groups (p<0.001, repeated measures ANOVA). Therefore, role of the interventions in relation to AE in blood donors could not be established.